Optogenetic induction of cortical spreading depression in anesthetized and freely behaving mice. Issue 5 (May 2017) - Houben, Thijs; Loonen, Inge CM; Baca, Serapio M; Schenke, Maarten; Meijer, Johanna H; Ferrari, Michel D; Terwindt, Gisela M; Voskuyl, Rob A; Charles, Andrew; van den Maagdenberg, Arn MJM; Tolner, Else A
Cortical spreading depression, which plays an important role in multiple neurological disorders, has been studied primarily with experimental models that use highly invasive methods. We developed a relatively non-invasive optogenetic model to induce cortical spreading depression by transcranial stimulation of channelrhodopsin-2 ion channels expressed in cortical layer 5 neurons. Light-evoked cortical spreading depression in anesthetized and freely behaving mice was studied with intracortical DC-potentials, multi-unit activity and/or non-invasive laser Doppler flowmetry, and optical intrinsic signal imaging. In anesthetized mice, cortical spreading depression induction thresholds and propagation rates were similar for invasive (DC-potential) and non-invasive (laser Doppler flowmetry) recording paradigms. Cortical spreading depression-related vascular and parenchymal optical intrinsic signal changes were similar to those evoked with KCl. In freely behaving mice, DC-potential and multi-unit activity recordings combined with laser Doppler flowmetry revealed cortical spreading depression characteristics comparable to those under anesthesia, except for a shorter cortical spreading depression duration. Cortical spreading depression resulted in a short increase followed by prolonged reduction of spontaneous active behavior. Motor function, as assessed by wire grip tests, was transiently and unilaterally suppressed following a cortical spreading depression. Optogenetic cortical spreading depression induction has significant advantages over current models in that multiple cortical spreading depression events can be elicited in a non-invasive and cell type-selective fashion.